2019
DOI: 10.1002/acn3.50820
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of a humanized anti‐IL‐2/IL‐15 receptor β chain in HAM/TSP

Abstract: Objective Human T cell lymphotropic virus 1 (HTLV‐1)‐associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a chronic, progressive, neurological disease. Chronic activation of CD8+ T cells, as evidenced by increased spontaneous lymphoproliferation and HTLV‐1‐specific cytotoxic T cells, has been demonstrated in HAM/TSP patients. Since IL‐2 and IL‐15 stimulate memory CD8+ T cell activity, these cytokines have been implicated in the immunopathogenesis of HAM/TSP. In this phase I trial, we evaluated the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“… 20 , 25 , 26 A number of drugs and monoclonal antibodies have been reported to suppress inflammation and activation of lymphocytes, evidenced by inhibitory effects on spontaneous lymphoproliferation and cytokine expression in ex vivo PBMC culture of patients with HAM/TSP 25 , 27 - 29 and have been used in clinical trials for patients with HAM/TSP. 17 , 30 , 31 Proliferation of T cells in HAM/TSP may also be associated with the immunopathogenesis of this disease because antigen-specific CD8 + T cells have been shown to be elevated in peripheral blood, even higher in the CSF, of patients with HAM/TSP, and have been shown to be present in CNS lesions. 5 , 32 - 34 Recently, teriflunomide has been reported to modulate oxidative phosphorylation and aerobic glycolysis in activated T cells via functional inhibition of complex III of the respiratory chain and preferentially reduce the proliferation of high-affinity T cells.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 25 , 26 A number of drugs and monoclonal antibodies have been reported to suppress inflammation and activation of lymphocytes, evidenced by inhibitory effects on spontaneous lymphoproliferation and cytokine expression in ex vivo PBMC culture of patients with HAM/TSP 25 , 27 - 29 and have been used in clinical trials for patients with HAM/TSP. 17 , 30 , 31 Proliferation of T cells in HAM/TSP may also be associated with the immunopathogenesis of this disease because antigen-specific CD8 + T cells have been shown to be elevated in peripheral blood, even higher in the CSF, of patients with HAM/TSP, and have been shown to be present in CNS lesions. 5 , 32 - 34 Recently, teriflunomide has been reported to modulate oxidative phosphorylation and aerobic glycolysis in activated T cells via functional inhibition of complex III of the respiratory chain and preferentially reduce the proliferation of high-affinity T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In HAM/TSP patients, alternative expressions of various inhibitory receptors, such as PD-1, CD244, and Tim-3, have been demonstrated on CD8 + T cells (Enose-Akahata et al 2009 ; Abdelbary et al 2011 ; Kozako et al 2011 ; Manuel et al 2013 ). Some reports showed PD-1 expression is upregulated in both infected T cells and CTL (Yasuma et al 2016b ; Enose-Akahata et al 2019 ) and these PD-1 + cells in CD8 + T cells showed CTL dysfunction in HAM/TSP patients (Manuel et al 2013 ). T cell immunoglobulin and ITIM domain (TIGIT), which is another inhibitory molecule and expressed on activated T cells and Treg cells, are also highly expressed with PD-1 in HAM/TSP patients (Yasuma et al 2016b ).…”
Section: Htlv-1 Virusmentioning
confidence: 99%
“…Hu-Mikβ1, which is a humanized monoclonal antibody against the β subunit shared by the IL-2 and IL-15 receptors (IL-2/IL-15Rβ; CD122), has been reported to inhibit abnormal T cell proliferation and HTLV-1-specific cellular immune responses by blocking IL-15 action in HAM/TSP patients (Azimi et al 1999 ; Enose-Akahata et al 2008 ). The treatment with Hu-Mikβ1 showed the inhibition of aberrant CD8 + T cell function in HAM/TSP patients although no clinical efficacy was observed (Enose-Akahata et al 2019 ). Raltegravir, which is an integrase inhibitor used for the treatment of HIV-1, was reported to reduce cell-free and cell-to-cell transmission of HTLV-1 in vitro (Seegulam and Ratner 2011 ).…”
Section: Htlv-1 Virusmentioning
confidence: 99%
“…A subset of memory CD8 + T cells, stem cell-like memory T cells (Tscm), has been reported to be identified as a naïve phenotype but express increased level of CD95, IL-2Rβ, CXCR3 and LFA-1 and have similar functions to memory T cells including the ability to proliferate rapidly and release inflammatory cytokines in response to antigen re-exposure [86]. Recently, it has been demonstrated that the frequency of Tscm was significantly increased in HAM/TSP patients compared to healthy controls, suggesting that an adequate number of functionally competent memory CD8 + T cells might be sustained through cytokine-driven homeostatic proliferation to achieve long-lived protection against chronic HTLV-1 infection [87]. Using a new high throughput sequencing technology, analysis of T cell receptor (TCR) repertoire recently revealed that HAM/TSP patients showed a higher clonal T cell expansion in peripheral blood compared to patients with multiple sclerosis and healthy controls [88].…”
Section: Csf Cellular Immune Responses In Ham/tspmentioning
confidence: 99%
“…Importantly, reduction in spasticity and motor disability was observed in 79% and 32% of HAM/TSP patients, respectively [141]. A humanized anti-IL-2/IL-15 receptor β chain (Hu-Mikβ1), mainly targeted to inflammatory CD8 + T cells, demonstrated inhibition of aberrant CD8 + T cell functions including spontaneous lymphoproliferation and degranulation and IFN-γ expression [87].…”
Section: Future Challengesmentioning
confidence: 99%